Shoulder Arthroscopy Principles and Practice - Milano, Giuseppe; Grasso, Andrea (Springer London : Imprint: Springer, 2014)
This comprehensive and stunningly illustrated textbook covers the entire spectrum of shoulder disease and arthroscopic techniques. It reviews the anatomy and the biomechanics of the shoulder, basic arthroscopic procedures, advanced reconstructive surgeries, and an overview on shoulder pathologies with a special focus on surgical approach. Shoulder Arthroscopy: Principles and Practice is a highly organized reference with all chapters following a standardized format: from detailed descriptions regarding epidemiology, pathophysiology, clinical findings, imaging, indication for treatment up to a step-by-step description of current surgical techniques, including tips and tricks on how to avoid the most common mistakes and complications. There is also an entire section dedicated to the evaluation of outcome measurements. The tips and techniques presented in this book are based on the Editor and his Contributors' individual experience. The book guides the orthopaedic resident and fellow who wants to focus on shoulder diseases, but it also represents a landmark reference for expert surgeons already involved in shoulder surgery.